Pemeriksaan Kesehatan Pada Lansia di Dusun Kandangan Rambipuji Jember: Pemeriksaan Kesehatan Pada Lansia di Dusun Kandangan Rambipuji Jember - Wijaya, Anas Fadli; Mutiurrohman, Achmad; Ikhsan, Ahmad Mufti; Putri, Diva Amalia; Hanifiyah, Fitroh; Rossa, Handita Emilia; Kamaliyah, Indy; M Syaifuddin; Wafa, Muhammad Ali; Soleha, Nurmaidatus; Maimunah, Siti; Holifah, Siti Nur; Sofia (Ruang Ide Publisher, 2024)
Elderly individuals are a vulnerable age group prone to various health issues due to the aging process, such as hypertension, diabetes mellitus, and uric acid disorders. Low health awareness and economic constraints lead to infrequent health check-ups among the elderly, resulting in missed opportunities for early disease detection. This community service activity aims to conduct health screenings for the elderly, focusing on blood pressure measurement, blood glucose testing, and uric acid levels in Dusun Kandangan, Pecoro Village, Rambipuji District, Jember Regency, on August 21, 2024. The methods employed include blood pressure measurement using a sphygmomanometer, blood glucose testing, and uric acid testing using test strips. Of the 27 elderly individuals examined, 15 were found to have hypertension, 8 showed symptoms of diabetes mellitus, and 10 had elevated uric acid levels. This activity successfully identified health issues among the elderly.